Dasaĩ and dual power among the Yakthumba - Philippe Sagant (Ateliers d'Anthropologie)
Dasaĩ is a Yakthumba popular festival. The cult of Durgā legitimates the authority of the political headmen, the subbā, who appeared after the Gurkha conquest (having been delegated by the “kings”, called hang). The hang was in fact an ordinary head of house (tumyang) like any other. The subbās seem to have taken over from the former kings. But because he enjoyed the favor of Nahangma, the yakthumba goddess of the mountain, he was recognized as primus inter pares (tum tumyang) and was brought to power. Nahangma is not present at Dasaĩ but is replaced by another goddess called Yuma (the grandmother) with whom she has always been fighting. But this does not mean she is not still worshipped in each house on her own dates. And just as Durgā and Yuma legitimate the subbā’s monopoly of power over arms, Nahangma legitimates this same power for each household head under the subbā; thus a contradiction arises. And so we find the Yakthumba living under the twofold antagonistic power of the gods (Durgā and Nahangma), which is the foundation of the twofold antagonistic power of men (subbā and tumyang). If this hypothesis is correct, then the hang of the past, also a head of house, has not disappeared, which is what the author has shown.